Overexpression of Global Regulator Talae1 Leads to the Discovery of New Antifungal Polyketides From Endophytic Fungus Trichoderma afroharzianum - Ding, Zhuang; Wang, Xiao; Kong, Fan-Dong; Huang, Hui-Ming; Zhao, Yan-Na; Liu, Min; Wang, Zheng-Ping; Han, Jun (Frontiers in Microbiology, 2020)
Transcription regulation caused by global regulators exerts important effects on fungal secondary metabolism. By overexpression of the global regulator Talae1 in a Ficus elastica-associated fungus Trichoderma afroharzianum, two structurally new polyketides (1 and 2) that were newly produced in the transformant were isolated and identified. Their structures, including the absolute configurations, were elucidated through a combination of HRMS, NMR, and ECD calculations. The growth inhibitory activities of compounds 1 and 2 were evaluated against four bacteria and six plant-pathogenic fungi. Compound 1 showed the highest antifungal activity against Botrytis cinerea and Fusarium oxysporum f. sp. nicotianae with MIC of 8 μg/mL. To the best of our knowledge, this is the first study to report on the application of the global regulator in T. afroharzianum to activate the biosynthesis of bioactive secondary metabolites.